Animal learning and cognition - Mackintosh, N. J. (Nicholas John), 1935- (Handbook of perception and cognition (2nd ed.), 1994)
How do animals learn? By what means can animals be conditioned? This volume of the acclaimed Handbook of Perception and Cognition, Second Edition, reviews such basic models as Pavlovian conditioning as well as more modern models of animal memory and social cognition. Sure to represent a benchmark of a vast literature from diverse disciplines, this reference work is a useful addition to any library devoted to animal learning, conditioning behavior, and interaction.